MATHEMATICAL MODELS FOR CALCULATING THE RESIDUAL LIFE OF THE RECOVERABLE COMPONENTS OF THE AIRCRAFT ELECTRONIC SYSTEM - Serhii Haievskyi; Іgor Kulakov; Oleksandr Shapovalov; Oleksander Timochko; Vladislava Pavlenko (Сучасний стан наукових досліджень та технологій в промисловості)
The subject matter of the article are the processes of functioning of the radio electronic system of a modern aircraft, its components, functional units and functional systems as an object for determining and calculating indicators of residual life. The goal is the analysis and improvement of the existing mathematical apparatus used to calculate the indicators of the residual resource of the aircraft radio-electronic system restored components. The tasks: To develop and generalize mathematical models for calculating the indicators of the residual life of the restored components of the aircraft radio-electronic system. Analyzed models are: models for the indicators of the residual life of the restored object of the aircraft radio-electronic system, the failure flow model with a finite number of minimal updates, reliability models of the "load-strength" type. The following results were obtained: Mathematical models have been developed for calculating the indicators of residual life and residual operating time of a recoverable product with one resource element with a complete restoration of component elements of the aircraft radio-electronic system. Conclusions. Mathematical models have been developed for calculating the indicators of the residual life and the residual operating time of a restored product with one resource element with a complete restoration of component elements. A generalization of these models for a product restored by several resource elements during their complete restoration is obtained. Calculated ratios are obtained for the indicators of the residual resource and the residual operating time of functional devices and functional systems with a finite number of minimal updates of resource elements. Relationships are obtained for determining the limiting number of minimal restorations of functional devices and functional systems of the aircraft radio-electronic system.